Traumatic Chance Fracture of Cervical Spine: A Rare Fracture Type and Surgical Management - Eghbal, Keyvan (Asian J Neurosurg, 2018)
Cervical spine chance fracture (flexion-distraction) is a rare type of fracture, and the surgical management remains a dilemma to the neurosurgeons as there is a paucity of evidence accordingly. We herein report a traumatic chance fracture of C7 fractures and its surgical management. A 33-year-old male was transferred to our center after being hit as pedestrian and was diagnosed to have a chance fracture of C7 and bilateral C7 root injury. He underwent open reduction of the deformity by posterior-only fixation of C5 and C6 with a lateral mass screw and T1 and T2 with pedicular screws. The neurological examination improved postoperatively, and the patients were neurologically intact after 6 months of treatment. Traumatic cervical spine chance fracture is extremely rare and can be managed surgically through posterior fixation and open reduction of the deformity. The best choice of treatment is limited by the paucity of the evidence and should be individualized.